Translationally controlled tumour protein TCTP is induced early in human colorectal tumours and contributes to the resistance of HCT116 colon cancer cells to 5-FU and oxaliplatin. Issue 1 (December 2017) - Bommer, Ulrich-Axel; Vine, Kara; Puri, Prianka; Engel, Martin; Belfiore, Lisa; Fildes, Karen; Batterham, Marijka; Lochhead, Alistair; Aghmesheh, Morteza
Abstract Background Translationally controlled tumour protein TCTP is an anti-apoptotic protein frequently overexpressed in cancers, where high levels are often associated with poor patient outcome. TCTP may be involved in protecting cancer cells against the cytotoxic action of anti-cancer drugs. Here we study the early increase of TCTP levels in human colorectal cancer (CRC) and the regulation of TCTP expression in HCT116 colon cancer cells, in response to treatment with the anti-cancer drugs 5-FU and oxaliplatin. Methods Using immunohistochemistry, we assessed TCTP levels in surgical samples from adenomas and adenocarcinomas of the colon, compared to normal colon tissue. We also studied the regulation of TCTP in HCT116 colon cancer cells in response to 5-FU and oxaliplatin by western blotting. TCTP mRNA levels were assessed by RT-qPCR. We used mTOR kinase inhibitors to demonstrate mTOR-dependent translational regulation of TCTP under these conditions. Employing the Real-Time Cell Analysis (RTCA) System and the MTS assay, we investigated the effect of TCTP-knockdown on the sensitivity of HCT116 cells to the anti-cancer drugs 5-FU and oxaliplatin. Results 1. TCTP levels are significantly increased in colon adenomas and adenocarcinomas, compared to normal colon tissue. 2. TCTP protein levels are about 4-fold upregulated in HCT116 colon cancer cells, in response to 5-FU and oxaliplatin treatment, whereas TCTP mRNA levels are down regulated. 3. mTOR kinase inhibitors prevented the up-regulation of TCTP protein, indicating that TCTP is translationally regulated through the mTOR complex 1 signalling pathway under these conditions. 4. Using two cellular assay systems, we demonstrated that TCTP-knockdown sensitises HCT116 cells to the cytotoxicity caused by 5-FU and oxaliplatin. Conclusions Our results demonstrate that TCTP levels increase significantly in the early stages of CRC development. In colon cancer cells, expression of this protein is largely upregulated during treatment with the DNA-damaging anti-cancer drugs 5-FU and oxaliplatin, as part of the cellular stress response. TCTP may thus contribute to the development of anti-cancer drug resistance. These findings indicate that TCTP might be suitable as a biomarker and that combinatorial treatment using 5-FU/oxaliplatin, together with mTOR kinase inhibitors, could be a route to preventing the development of resistance to these drugs.